Emotion dysregulation and negative affect: Laboratory and EMA investigations in smokers. (June 2018) - MacIntyre, Jessica M.; Ruscio, Aimee C.; Brede, Emily; Waters, Andrew J.
Abstract: Introduction: Difficulties in emotion regulation are associated with addictive behaviors, including smoking. Difficulties in emotion regulation may underlie large, rapid changes in negative affect that can increase likelihood of relapse. We investigated the association between emotion regulation ability and negative affect in smokers assessed both in the laboratory and in the field using Ecological Momentary Assessment. Methods: Adult community smokers ( N  = 44) carried a personal digital assistant (PDA) for two weeks and were instructed to complete assessments of negative affect multiple times per day. Participants were instructed that they could smoke as much or as little as they liked. The Difficulties in Emotion Regulation Scale (DERS) and the Positive and Negative Affect Schedule (PANAS) were completed at three lab visits. Results: Participants with higher average DERS scores reported greater negative affect at lab visits. When a participant reported a DERS score at a lab visit higher than their individual average, they also reported higher negative affect at that lab visit. Participants with higher baseline DERS scores reported more labile negative affect during EMA than those with lower baseline DERS scores, and they also reported a higher maximum level of negative affect during EMA. Discussion and conclusions: Overall, the findings suggest that changes in emotion regulation are associated with negative affect and that emotion regulation ability is related to both the intensity and lability of negative affect. A better understanding of momentary changes in emotion regulation and negative affect may lead to improved interventions for preventing substance use relapse. Highlights: Emotion regulation show variability, and changes in emotion regulation are associated with changes in negative affect Emotion regulation ability is associated with the intensity of negative affect assessed using EMA Emotion regulation ability is associated with the lability of negative affect assessed using EMA